Determination of residual stress distributions in polycrystalline alumina using fluorescence microscopy. (5th October 2016) - Michaels, Chris A.; Cook, Robert F.
Abstract: Maps of residual stress distributions arising from anisotropic thermal expansion effects in a polycrystalline alumina are generated using fluorescence microscopy. The shifts of both the R1 and R2 ruby fluorescence lines of Cr in alumina are used to create maps with sub-μm resolution of either the local mean and shear stresses or local crystallographic a - and c -stresses in the material, with approximately ± 1 MPa stress resolution. The use of single crystal control materials and explicit correction for temperature and composition effects on line shifts enabled determination of the absolute values and distributions of values of stresses. Temperature correction is shown to be critical in absolute stress determination. Experimental determinations of average stress parameters in the mapped structure are consistent with assumed equilibrium conditions and with integrated large-area measurements. Average crystallographic stresses of order hundreds of MPa are determined with characteristic distribution widths of tens of MPa. The stress distributions reflect contributions from individual clusters of stress in the structure; the cluster size is somewhat larger than the grain size. An example application of the use of stress maps is shown in the calculation of stress-intensity factors for fracture in the residual stress field. Graphical abstract: Highlights: Measurement of Cr fluorescence line positions in polycrystalline alumina enabled residual stress components to be mapped. Spatial resolution of the maps is sub micrometer and stress resolution is about one megapascal. Fluorescence intensity maps show that residual stress variations occur over length scales larger than the grain size. Temperature and composition corrections are critical for absolute stress value determination.